Romper El Silencio: Aproximaciones A La Problemática De La Violencia Intrafamiliar En El Ecuador - Luis, Alejandro Hernández; Avendaño, Ana Veloz; Peñafiel, Tania Zabala (European Scientific Journal, ESJ, 2017)
This paper aims to make a multidisciplinary approach of domestic violence, considering social, cultural, political and socioeconomic factors that encourage and increase the risk of a woman to suffer any kind of violence. Also, from a theoretical approach, there is a relationship of structural gender inequality as a cause of coercitive control to the woman and how cultural patterns play different roles between men and women, which underlie a deep inequality rarely visible, analyzed and discussed in the legal instruments and even the terminology used to refed to this problema. All this suggests the paradox of the â€œduality of structureâ€. In that sense, the case of study is the Ecuadorian, existing legislation and the corresponding evolution in this matter is reviewed, to asssess if it serves to the key factors that are studied in this work and harm the integrity of women in all possible areas. Finally, because of the limited statistical information for case analysis, some preliminary conclusions are made.